A general White–Box strategy for designing thermoelectric cooling system. Issue 11 (20th May 2022) - Zhu, Kang; Deng, Biao; Qian, Xin; Wang, Yupeng; Li, Huan; Jiang, Peng; Yang, Ronggui; Liu, Weishu
Abstract: Thermoelectric cooling (TEC) is critically important in thermal management of laser modules or chips and potentially for personalized thermoregulation. The formulae for efficiency in standard textbooks can only describe the performance of a TEC module with ideal thermal conditions, that is, fixed terminal temperatures, but are unable to deal with a real TEC system where heat transfer at its interfaces with the heat source and sink are finite and with thermal resistances. Here, we define the TEC system‐level performance indices, that is, the maximum cooling power, temperature difference, and coefficient of performance, by introducing a set of explicit formulae. The external heat transfer conditions are taken into account as dimensionless thermal resistance parameters. With these formulae, the TEC system performances are evaluated elegantly with errors well within ±5% over broad operating conditions. We further optimize the cooling power and the coefficient of performance in practical scenarios and establish a general White–Box design procedure for TEC systems, which enables a transparent design process and straightforward analysis of performance bottlenecks. A set of cooling experiments are performed to validate the analytical model and to illustrate the dependence of system design on realistic thermal conditions. By choosing the suitable TEC module parameter under given external heat transfer conditions, the cooling power can be improved by more than 100%. This work sheds some light on the integral design of TEC systems for broad applications to take full advantage of the advanced thermoelectric materials in the cooling field. Abstract : In spite of its broad market in thermal management, the design and evaluation of thermoelectric cooling systems remain complicated. In this work, a general White–Box design strategy for thermoelectric cooling systems is proposed based on a newly developed analytical framework, which would take full advantage of material innovations and be beneficial to the widespread applications of the thermoelectric cooling technology.